2018
DOI: 10.1007/s11046-018-0258-5
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia in Adults at a Tertiary Hospital in China: Clinical Characteristics, Species Distribution, Resistance, and Outcomes

Abstract: Candida albicans was the most frequent cause of candidemia at a large tertiary hospital in China, but antifungal resistance is a growing concern among non-albicans Candida species. The mortality rate of patients treated with ineffective antifungal agents based on in vitro susceptibilities was similar to that of patients who received no treatment at all, and delayed initiation of antifungal treatment was associated with increased risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
12
4
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 58 publications
8
12
4
4
Order By: Relevance
“…In accordance with other studies [17-19, 24, 25, 30, 32, 35, 36], C. albicans was the most common cause of candidaemia in the whole hospital, but the proportion of non-C. albicans infections was higher than that of C. albicans infections. Moreover, the proportions of C. glabrata in surgical, internal medicine and paediatric wards were the highest, which is different from other studies in China [18,19,[35][36][37] but similar to other studies in other countries [4,22,27,29,32]. This may be due to the large number of elderly patients and the increasing use of azole antifungal agents.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In accordance with other studies [17-19, 24, 25, 30, 32, 35, 36], C. albicans was the most common cause of candidaemia in the whole hospital, but the proportion of non-C. albicans infections was higher than that of C. albicans infections. Moreover, the proportions of C. glabrata in surgical, internal medicine and paediatric wards were the highest, which is different from other studies in China [18,19,[35][36][37] but similar to other studies in other countries [4,22,27,29,32]. This may be due to the large number of elderly patients and the increasing use of azole antifungal agents.…”
Section: Discussioncontrasting
confidence: 90%
“…Our data showed that the median age of patients with candidaemia and the proportion of males were similar to those in other studies [8,[18][19][20][21][22][23]. Moreover, our study showed that the patients with candidaemia were hospitalised mostly in internal medicine wards, which is different from other studies that reporting hospitalisation mainly in ICU wards [8,22,[24][25][26][27], but similar to other studies [28][29][30][31].…”
Section: Discussionsupporting
confidence: 84%
“…In accordance with other studies [17-19, 24, 25, 30, 32, 35, 36], C. albicans was the most common cause of candidaemia in the whole hospital, but the proportion of non-C. albicans infections was higher than that of C. albicans infections. Moreover, the proportions of C. glabrata in surgical, internal medicine and paediatric wards were the highest, which is different from other studies in China [18,19,[35][36][37] but similar to other studies in other countries [4,22,27,29,32]. This may be due to the large number of elderly patients and the increasing use of azole antifungal agents.…”
Section: Discussioncontrasting
confidence: 88%
“…Moreover, FCA was highly active against all Candida species in paediatric patients and could be used in paediatric patients with candidaemia as a rst-line agent. In the whole hospital, the resistance rate to azole was higher than those reported in other regions [18,19,36] and countries [17,19,25,29,30,34]. This may be related to the long-term use of empirical prophylactic drugs by clinicians.…”
Section: Discussionmentioning
confidence: 70%
“…This phenomenon is most likely due to the widespread and increasingly common utilization of echinocandins, especially as they are currently recommended as the first-line antifungal for treatment of invasive candidiasis ( 9 12 ). After C. albicans , C. parapsilosis is the second or third most common cause of invasive candidiasis depending on the geographical location ( 5 , 13 , 14 ). In fact, previous exposure to echinocandins is a risk factor for C. parapsilosis infections, as this species manifests naturally higher MIC values to the three clinically available echinocandins (caspofungin [CAS], anidulafungin [AND], and micafungin [MICA]) compared to other Candida species ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%